2000
DOI: 10.4049/jimmunol.164.10.5508
|View full text |Cite
|
Sign up to set email alerts
|

Human Dendritic Cells Transfected with RNA Encoding Prostate-Specific Antigen Stimulate Prostate-Specific CTL Responses In Vitro

Abstract: Although immunological tolerance to self Ags represents an important mechanism to prevent normal tissue injury, there is growing evidence that tolerance to tumor Ags, which often represent normal peripherally expressed proteins, is not absolute and can be effectively reverted. Prostate-specific Ag (PSA) is a self Ag expressed by both normal and malignant prostatic epithelium, and therefore offers a unique opportunity to examine the ability of self Ags to serve as specific CTL targets. In this study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(97 citation statements)
references
References 24 publications
3
92
1
1
Order By: Relevance
“…We here applied an efficient approach to load APC with N-terminally truncated LMP1 using in vitro transcribed mRNA introduced via electroporation. Such mRNA-loaded DC have been proven to be able to stimulate the immune system in vitro and in vivo [21,22,[38][39][40][41][42]. In addition, this provides a very safe tool for human clinical studies, as mRNA is not immunogenic, has a relatively short half-life, and lacks the potential for integration into the host genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We here applied an efficient approach to load APC with N-terminally truncated LMP1 using in vitro transcribed mRNA introduced via electroporation. Such mRNA-loaded DC have been proven to be able to stimulate the immune system in vitro and in vivo [21,22,[38][39][40][41][42]. In addition, this provides a very safe tool for human clinical studies, as mRNA is not immunogenic, has a relatively short half-life, and lacks the potential for integration into the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that APC transduced with in vitro transcribed mRNA encoding certain Ag are potent inducers of CTL specific to tumor-associated Ag [21][22][23][24], even overcoming immunological tolerance to self Ag [25]. The advantages seem to derive from (1) complete deletion of antigenicity of vector backbone sequences; (2) highly reproducible yields with in vitro transcription; (3) high efficiency of transduction using electroporation.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer vaccines may represent an alternative form of therapy for such patients. It has been shown that autologous dendritic cells (DCs) pulsed with peptides specific for PSA (Heiser et al, 2000), prostate-specific membrane antigen (PSMA) (Tjoa et al, 1996) or telomerase reverse transcriptase (TERT) (Vonderheide et al, 1999) are capable of stimulating potent CTL responses in vitro and data from clinical trials are now available (Heiser et al, 2002;Kaufman et al, 2004). Since prostate cancer cells are genetically unstable and as such represent 'shifting targets' (Shaffer and Scher, 2003), single-agent vaccines may result in selection of genetic variants that escape the immune attack.…”
mentioning
confidence: 99%
“…For in vitro transcription, pcDNA3-EGFP and pcDNA3-CEA plasmids were linearized with Sma I, purified by phenol/chloroform extraction and ethanol precipitation and used as DNA templates [39]. In vitro transcription was performed using T7 RNA polymerase (mMESSAGE mMACHINE kit; Ambion, Austin, TX) according to the manufacturer's instructions.…”
Section: Rna Electroporation Of B Cells and DCmentioning
confidence: 99%